Time Dysperception Perspective for Acquired Brain Injury - Piras, Federica; Piras, Fabrizio; Ciullo, Valentina; Danese, Emanuela; Caltagirone, Carlo; Spalletta, Gianfranco (Frontiers in Neurology, 2014)
Distortions of time perception are presented by a number of neuropsychiatric illnesses. Here we survey timing abilities in clinical populations with focal lesions in key brain structures recently implicated in human studies of timing. We also review timing performance in amnesic and traumatic brain injured patients in order to identify the nature of specific timing disorders in different brain damaged populations. We purposely analyzed the complex relationship between both cognitive and contextual factors involved in time estimation, as to characterize the correlation between timed and other cognitive behaviors in each group. We assume that interval timing is a solid construct to study cognitive dysfunctions following brain injury, as timing performance is a sensitive metric of information processing, while temporal cognition has the potential of influencing a wide range of cognitive processes. Moreover, temporal performance is a sensitive assay of damage to the underlying neural substrate after a brain insult. Further research in neurological and psychiatric patients will clarify whether time distortions are a manifestation of, or a mechanism for, cognitive and behavioral symptoms of neuropsychiatric disorders.